The Influence of Emotional Intelligence on Job Burnout and Job Performance: Mediating Effect of Psychological Capital - Gong, Zhun; Chen, Yuqi; Wang, Yayu (Frontiers in Psychology, 2019)
How does emotional intelligence (EI) affect job performance and job burnout? Direct or indirect? What role does psychological capital play? This study surveyed 450 employees of various enterprises through questionnaires. Results are as follow: (1) Employees’ emotional intelligence has a positive predictive effect on psychological capital and job performance, and it is negatively correlated with job burnout. (2) Psychological capital has a negative predictive effect on job burnout and a positive predictive effect on job performance. (3) Psychological capital plays a mediating role in the relationship between emotional intelligence and job burnout/performance. Results of this study may contribute to develop emotional intelligence theories in organizational behaviour field. As for enterprises, improving the emotional intelligence of employees will help to improve their psychological capital, and high psychological capital will lead to positive job performance and less job burnout.